2013
DOI: 10.1002/bip.22333
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and tethering of DNA‐binding domains in σ54 transcriptional activators

Abstract: We compare the structure, activity and linkage of DNA binding domains from σ54 transcriptional activators, and discuss how the properties of the DNA binding domains and the linker to the neighboring domain are affected by the overall properties and requirements of the full proteins. These transcriptional activators bind upstream of specific promoters that utilize σ54-polymerase. Upon receiving a signal the activators assemble into hexamers, which then, through ATP hydrolysis, drive a conformational change in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…In NtrC residues identified as important for DNA binding through mutagenesis (R456, N457, R461) 38 are in the recogniton helix, and are predicted to point into the groove, the difference in spacing of the helices 39 leaves unclear what bending is induced by NtrC and which residues are responsible. Localized bending may affect the cooperativity of binding activators at adjacent sites, and hence may affect potency of activator sites.…”
Section: Discussionmentioning
confidence: 99%
“…In NtrC residues identified as important for DNA binding through mutagenesis (R456, N457, R461) 38 are in the recogniton helix, and are predicted to point into the groove, the difference in spacing of the helices 39 leaves unclear what bending is induced by NtrC and which residues are responsible. Localized bending may affect the cooperativity of binding activators at adjacent sites, and hence may affect potency of activator sites.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectroscopy data showed that hexamer is favored over heptamer in fulllength constructs of NtrC4, an EBP related to NtrC1 (Batchelor et al 2009). The receiver domain forms stable homodimers, and the C-terminal DNA-binding domain directs assembly of four protomers in a tandem array on ''enhancers'' (Doucleff et al 2005;Vidangos et al 2013). However, this potential artifact underscores the stabilization of split hexamer rings of EBP and does not diminish the evidence for g-phosphate-directed asymmetry in this structural state.…”
Section: Crucial Asymmetry In Bebp Atpase Ring Genes and Development 2505mentioning
confidence: 99%
“…glnAp2 transcription is activated by NtrC in response to nitrogen limitation (2933). NtrC molecules are dimeric in their inactive state.…”
Section: Introductionmentioning
confidence: 99%
“…σ 54 RNAP binds to the −24–−12 region at one face of the double helix (11). NtrC hexamers catalyze σ 54 RNAP via DNA looping; the catalysis reaction takes place at approximately −12 region and the edge of the central pore of NtrC hexamer (10,11,29,38). Such a regulatory mode—activators at remote enhancers direct transcription initiation though DNA looping—is similar to that in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation